TRANSLATION ERRORS AS A CONSEQUENCE OF INTERFERING INFLUENCES ON UKRAINIAN ELECTRIC POWER ENGINEERING TERMINOLOGY - Kharchuk, Liliia Valeriivna (Acta Neophilologica, 2019)
This study analyzes one of the periods of the Ukrainian electric power engineering system development (period of distortion) with the purpose of detecting typical errors in translation of terminology from Russian into Ukrainian. To date, scientific and academic literatures remain Russified; a violation of linguistic norms on the lexical and derivational levels is quite common. We consider that recommendations of linguists concerning academic and technical translations will be valuable for specialist in the electric power industry and will contribute to a harmonious development of Ukrainian electric power engineering terminology.